Ozone anomalies over the polar regions during stratospheric warming events - G. Shi; W. Krochin; E. Sauvageat; G. Stober (Atmospheric Chemistry and Physics, 2024)
The impact of major sudden stratospheric warming (SSW) events and early final stratospheric warming (FSW) events on ozone variations in the middle atmosphere in the Arctic is investigated by performing microwave radiometer measurements above Ny-Ålesund, Svalbard (79° N, 12° E), with GROMOS-C (GRound-based Ozone MOnitoring System for Campaigns). The retrieved daily ozone profiles during SSW and FSW events in the stratosphere and lower mesosphere at 20–70 km from microwave observations are cross-compared to MERRA-2 (Modern-Era Retrospective Analysis for Research and Applications, version 2) and MLS (Microwave Limb Sounder). The vertically resolved structures of polar ozone anomalies relative to the climatologies derived from GROMOS-C, MERRA-2, and MLS shed light on the consistent pattern in the evolution of ozone anomalies during both types of events. For SSW events, ozone anomalies are positive at all altitudes within 30 d after onset, followed by negative anomalies descending in the middle stratosphere. However, positive anomalies in the middle and lower stratosphere and negative anomalies in the upper stratosphere at onset are followed by negative anomalies in the middle stratosphere and positive anomalies in the upper stratosphere during FSW events. Here, we compare results by leveraging the ozone continuity equation with meteorological fields from MERRA-2 and directly using MERRA-2 ozone tendency products to quantify the impact of dynamical and chemical processes on ozone anomalies during SSW and FSW events. We document the underlying dynamical and chemical mechanisms that are responsible for the observed ozone anomalies in the entire life cycle of SSW and FSW events. Polar ozone anomalies in the lower and middle stratosphere undergo a rapid and long-lasting increase of more than 1 ppmv close to SSW onset, which is attributed to the dynamical processes of the horizontal eddy effect and vertical advection. The pattern of ozone anomalies for FSW events is associated with the combined effects of dynamical and ...